Estimation of Bond Strength based on Corroded Hinge Beam Specimens: Assessment of Design Guidelines and Analytical Models - Bhushan, Bharat; Arora, Harish Chandra; Kumar, Aman; Kumar, Prashant; Sharma, Surabhi; Sharma, Madhu (Periodica Polytechnica Civil Engineering, 2024)
The bond between steel and concrete enhances the structural integrity of the building and ensures a cohesive force-resistant system, facilitating composite action between the rebars and concrete. This composite action, in turn, ensures the longevity of the reinforced concrete (RC) structure. The current study focuses on evaluating the performance and comparing design guidelines and analytical models pertaining to hinge beams and pull-out test specimens. The bond strength between concrete and steel was determined by validating 124 experimental datasets collected from the literature. These datasets were based on hinge and pocket beam specimens with varying degrees of corrosion. To facilitate comparison, the international design guidelines and analytical models were designated as G-1 and G-2, respectively. The results indicate that Model M-6 from G-1 and Model M-10 from G-2 outperformed all other models within their respective groups. Upon comparing these two models, M-6 appears to be superior based on selected performance indices. Model M-6 demonstrated an R-value of 0.3275, MAE of 2.29 MPa, RMSE of 2.76 MPa, and MAPE of 39.12% sequentially. Additionally, sensitivity analysis based on the collected dataset was conducted to assess the impact of each parameter. This study offers a comprehensive analysis of bond strength between steel and concrete in RC structures, focusing on hinge beams and pull-out test specimens with varying degrees of corrosion. It introduces superior models for performance evaluation and comparative analysis, highlighting Model M-6 as a novel and robust approach with significant potential for enhancing structural design guidelines.